Issues in contemporary oil paint - Burnstock, Aviva; de Keijzer, Matthijs; Krueger, Jay; Learner, Tom; Tagle, de, Alberto; Heydenreich, Gunnar; van den Berg, Klaas Jan (Springer International Publishing, 2014)
This volume represents 27 peer-reviewed papers presented at the ICOP 2013 symposium which will help conservators and curators recognise problems and interpret visual changes on paintings, which in turn give a more solid basis for decisions on the treatment of these paintings.  The subject matter ranges from developments of paint technology, working methods of individual artists, through characterisation of paints and paint surfaces, paint degradation vs. long time stability, to observations of issues in collections, cleaning and other treatment issues as well as new conservation approaches.